Desde el discurso médico: perspectivas sobre las disfunciones sexuales femeninas y masculinas en el Perú contemporáneo - Olivera, Skarlet (2021)
In historically heteropatriarchal societies such as Peru, the issue of sexuality is framed in a context of myths, taboos, and misinformation, which is, in part, constructed by processes of medicalization. Within this, sexual dysfunctions are conceived as disorders or pathologies that require diagnosis and treatment by specialized personnel. This research aims to explain the ways in which sexual dysfunctions, both female and male, are currently approached from the medical discourse. Through an eminently qualitative methodology that has health professionals as a sample, the main findings refer to the causes of sexual dysfunctions and the gender approach present in the entire process of diagnosis, treatment, and perception. As a cause, the social factor plays an important but always circumscribed role in what is considered psychological or psychosomatic. Likewise, the generational and gender aspect of the interviewees is essential to explain differences regarding their medical and heteronormative perspectives. Finally, it is concluded that the perception of sexual dysfunction is affected by constructions of femininity and masculinity typical of hetero-cis-patriarchal systems.